Dance Movement Therapy Osho Kundalini Sebagai Media Untuk Menurunkan Gejala Kecemasan, Stres, dan Depresi Pada Penyandang Disabilitas Mental - Tinon Citraning Harisuci; Vikri Islah Khafidz; Faricha Annisa; Fito Uli Huda (Jayapangus Press, 2026)
Individuals with mental disabilities are vulnerable to anxiety, stress, and depression that affect emotional and social functioning. This study aimed to evaluate the effect of Dance Movement Therapy (DMT) accompanied by Osho Kundalini music on reducing symptoms of anxiety, stress, and depression. The study employed a pre-experimental one-group pretest–posttest design involving 15 participants residing at Muria Jaya Social Service Center. Data were collected using the Depression Anxiety Stress Scale (DASS), observation, and interviews conducted before and after the intervention. The intervention integrated expressive movement, rhythmic stimulation, relaxation, and silent meditation to facilitate emotional release and enhance body awareness and psychological regulation. Statistical analysis indicated reductions in anxiety (t = 24.29), stress (t = 21.66), and depression (t = 18.51) scores after the intervention, with statistically significant differences and effect sizes indicating practical intervention impact. Although the research design limits causal inference due to the absence of a control group, the findings contribute empirical evidence regarding the potential of Osho Kundalini-based DMT as an applicable psychosocial intervention for individuals with mental disabilities in social care settings.